Gingival diseases: plaque induced and non-plaque induced: Penyakit gingiva: induksi plak dan induksi non-plak - Daniel Tetan-el; Andi Mardiana Adam; Eri Hendra Jubhari (Makassar Dental Journal, 2021)
Background: Gingival inflammation is not always caused by plaque buildup on the surface of teeth, but can also be caused by non-plaque factors and often shows a typical clinical picture. This review aims to describe various gingival diseases caused by plaque and non-plaque. Method: Review of various literature is conducted to find out various diseases in gingiva. A total of 38 literatures were collected from several electronic data sources using the combination search keywords "gingiva" and "periodontal disease". Results: Based on the review of the literature, gingiva diseases caused by non-plaque factors include bacterial infections, fungi, viruses, genetically derived gingiva lesions, and some mukokutan abnormalities that manifest as gingiva inflammation. In addition, other examples of non-plaque induced gingiva inflammation are allergic and traumatic lesions. Conclusion: Dental plaque-induced gingivitis has a variety of clinical signs and symptoms, and local predisposition factors and systemic modification factors can affect their area, severity, and development. Gingival diseases caused by non-plaque include a variety of conditions that are not caused by plaque and usually do not heal after plaque removal. Such lesions may be a manifestation of systemic conditions or may be localized in the oral cavity.